Efficacy of repetitive transcranial magnetic stimulation for disorders of consciousness: a retrospective cohort study - Zhang, Shiqiang; Liu, Shengdong; Gu, Chencong; Zhang, Ruijuan; Zhang, Yushan; Wang, Mingchen; Xu, Xiaodong (Frontiers in Neurology, 2025)
ObjectiveTo evaluate the efficacy and safety of repetitive transcranial magnetic stimulation (rTMS) in the treatment of patients with disorders of consciousness (DoC) in a real-world setting, and to analyze the relevant factors affecting efficacy.MethodUsing a single-center retrospective cohort study design based on a hospital information system, we reviewed all patients with DoC presenting to the rehabilitation unit of our hospital between October 2019 and October 2024. Efficacy was assessed using the Glasgow Coma Scale (GCS), with the presence or absence of rTMS as an exposure factor.ResultsThe exposed group did not significantly improve the GCS scores of patients with DoC compared to the non-exposed group. The Subgroup analysis showed that rTMS improved the level of consciousness in patients with stroke compared to the non-exposed group (p < 0.05), but there was no statistical significance in the comparison between the groups of patients with traumatic brain injury. Binary logistic regression analyses showed that shorter disease duration, injury at non-brain stem sites, higher pretreatment GCS scores, earlier timing of intervention, and combined use of acupuncture, amantadine, piracetam, and Suhexiang Pill were independent factors influencing the good prognosis of DoC patients.ConclusionrTMS did not significantly improve the GCS scores of patients with DoC. However, it may improve the level of consciousness of patients with stroke-induced or moderate DoC. Nevertheless, this conclusion requires validation through rigorous, standardized, large-sample randomized controlled trials (RCTs).